Effects of soil water depletion on the water relations in tropical kudzu - Netto, Adaucto Bellarmino de Pereira; Magalhães, Antonio Celso Novaes de; Pinto, Hilton Silveira (Pesquisa Agropecuaria Brasileira, 1999)
Tropical kudzu (Pueraria phaseoloides (Roxb.) Benth., Leguminosae: Faboideae) is native to the humid Southeastern Asia. Tropical kudzu has potential as a cover crop in regions subjected to dryness. The objective of this paper was to evaluate the effect of soil water depletion on leaflet relative water content (RWC), stomatal conductance (g) and temperature (TL) in tropical kudzu. RWC of water-stressed plants dropped from 96 to 78%, following a reduction in SWC from 0.25 to 0.17 g (H2O).g (dry soil)-1. Stomatal conductance of stressed plants decreased from 221 to 98 mmol.m-2.s-1, following the reduction in soil water content (SWC). The day after re-irrigation, g of water stressed plants was 15% lower than g of unstressed plants. Differences in TL between water-stressed and unstressed plants (DTL) rose linearly from 0.1 to 2.2oC following progressive water deficit. RWC and TL of water-stressed plants paralled RWC and TL of unstressed plants the day after re-irrigation. The strong decrease in SWC found in this study only induced moderate water stress in tropical kudzu. In addition, tropical kudzu recover rapidly from the induced water stress after the re-irrigation.